Black sexualities : probing powers, passions, practices, and policies - Battle, Juan, 1968-; Barnes, Sandra L. (Book collections on Project MUSE., 2010)
Contains twenty articles in which various authors explore issues in the field of Black sexualities, covering identity theories and frameworks; descriptions, depictions, and responses; citizenship, activism, and legal dynamics; systemic and personal stresses; and the life course.